Solvent Evaporation as an Efficient Microencapsulating Technique for Taste Masking in Fast Disintegrating Oral Tablets - Nagina Gulab Belali; Anis Yohana Chaerunisaa (Universitas Padjadjaran (Unpad), 2019)
Microencapsulation is an extensively used technology of present era, that has been applied to various fields like pharmaceutical industry, agriculture, cosmetics and food technology. With the help of which liquid or solid material can be encapsulated inside a polymeric coating film for various reasons such as taste masking, control release and enhancing stability and etc. Microencapsulation can be achieved with different approaches and methods but one of the popular and frequently used feasible method is Solvent evaporation. Solvent evaporation is based on emulsification, solvent evaporation and extraction of microspheres, recently many variations have been made in this technology to improve the yield and properties of microspheres. Solvent evaporation has been widely used in microencapsulating for different purposes one of which is taste masking of bitter drugs in fast disintegrating oral tablets, for pediatric and geriatric use. FDTs are center of attraction due to their merits and feasibility of use for people with problem of dysphagia at the same time, it can also improve bioavailability and time of action of drugs. The main focus of current review is use of solvent evaporation technique for taste masking of bitter drugs in production of fast disintegrating oral tablets. In this review, we will summarize uses, novelties and variations in Solvent Evaporation technique, preparation technique, materials used, merits and demerits of this method over other microencapsulation method in taste masking.Keywords: Microencapsulation, Solvent Evaporation, FDTs, extraction, microspheres